الاحكام المتعلقة بالعملات الرقمية ( الافتراضية ) - باي نصر الدين; طباخ مراد; بن لسبط لدمية (جامعة عمار ثليجي الاغواط, 2024)
الملخص: يعالج البحث نازلة من النوازل الفقهية وهي العملات الرقمية والتي أصبحت تشغل المؤسسات المالية، مع ما يصاحبها من سلبيات عديدة، رغم اعتبارها واحدة من وسائل التداول المالي الحديثة في كثير من دول العالم، ولذا جاء هذا البحث ليسلط الضوء على العملات الرقمية وبيان تعريفها ونشأتها وأول ظهور لها، وبيان مزاياها ومخاطرها والأحكام الفقهية المتعلقة بها من حيث جريان الربا فيها وجريان الزكاة فيها مع بيان الغرر والجهالة، وكذلك معرفة حقيقة المحافظ الإلكترونية ومدى اعتبارها حرزا، وبيان حكم التعامل بها شرعا وقانونا ولنتوصل أخيرا إلى أرجح الأقوال في حكم التعامل على صورتها الحالية. Summary: The research addresses a contemporary jurisprudential issue, which is digital currencies. These currencies have come to occupy financial institutions, accompanied by numerous negatives, despite being considered one of the modern financial trading methods in many countries around the world. Therefore, the research aims to shed light on digital currencies, explaining their definition, origin, first appearance, advantages, risks, and the related jurisprudential rulings, such as the applicability of usury and zakat. It also aims to clarify the purpose and ambiguity, as well as to understand the reality of electronic wallets and the extent to which they are considered a safeguard, and to explain the legal and religious rulings on dealing with them. Finally, it arrives at the most likely opinions regarding the ruling on dealing with them in their current form.
دراسة مقارنة بين الفقه و القانون